Political theory and the European constitution - Dobson, Lynn.; Føllesdal, Andreas (London ; New York : Routledge, 2004)
This timely volume provides one of the first critical assessments of the draft Constitution (released by the Convention on the future of Europe) from the vantage point of political theory.
Introduction / Lynn Dobson and Andreas Føllesdal -- Is Euro-federalism a solution or a problem? / Phillippe C. Schmitter -- The EU as a self-sustaining federation / David McKay -- A union of peoples? diversity and the predicaments of a multinational polity / Peter A. Kraus -- The good, the bad and the ugly / Richard Bellamy and Justus Schönlau -- Europe--united under God? or not? / Tore Vincents Olsen -- The open method of co-ordination in the European convention / Myrto Tsakatika -- Conceptions of freedom and the European constitution / Lynn Dobson -- The constitutional labelling of "the democratic life of the EU" / Stijn Smismans -- Transparency and legitimacy / Daniel Naurin -- An institutional dialogue on common principles / Claudia Attucci -- Motivating judges / Roberto Gargarella -- Conclusion / Andreas Føllesdal and Lynn Dobson.
Includes bibliographical references and index.
Print version record.
English.
eBooks on EBSCOhost
Keywords: Constitutional law -- European Union countries; Droit constitutionnel -- Pays de l'Union européenne.; LAW -- Constitutional; LAW -- Public; Constitutional law; European Union countries